Human papillomavirus detection in cervical neoplasia attributed to 12 high-risk human papillomavirus genotypes by region (2016)
Background: We estimated the proportion of cervical intraepithelial neoplasia (CIN) cases attributed to 14 HPV types, including quadrivalent (qHPV) (6/11/16/18) and 9-valent (9vHPV) (6/11/16/18/31/33/45/52/58) vaccine types, by region. Methods: Women ages 15-26 and 24-45 years from 5 regions were enrolled in qHPV vaccine clinical trials. Among 10,706 women (placebo arms), 1539 CIN1, 945 CIN2/3, and 24 adenocarcinoma in situ (AIS) cases were diagnosed by pathology panel consensus. Results: Predominant HPV types were 16/51/52/56 (anogenital infection), 16/39/51/52/56 (CIN1), and 16/31/52/58 (CIN2/3). In regions with largest sample sizes, minimal regional variation was observed in 9vHPV type prevalence in CIN1 (~50%) and CIN2/3 (81-85%). Types 31/33/45/52/58 accounted for 25-30% of CIN1 in Latin America and Europe, but 14-18% in North America and Asia. Types 31/33/45/52/58 accounted for 33-38% of CIN2/3 in Latin America (younger women), Europe, and Asia, but 17-18% of CIN2/3 in Latin America (older women) and North America. Non-vaccine HPV types 35/39/51/56/59 had similar or higher prevalence than qHPV types in CIN1 and were attributed to 2-11% of CIN2/3. Conclusions: The 9vHPV vaccine could potentially prevent the majority of CIN1-3, irrespective of geographic region. Notwithstanding, non-vaccine types 35/39/51/56/59 may still be responsible for some CIN1, and to a lesser extent CIN2/3. © 2016 The Authors.